2017
DOI: 10.1093/arclin/acx035
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Mind and Executive Functioning Following Stroke

Abstract: A reduction in the ability to attribute mental states to others following right hemisphere stroke may adversely affect psychosocial functioning, disrupt interpersonal relationships, and lead to reduced quality of life. The clinical importance of these findings, implications for clinical practice and future research are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…In stroke patients, impairments in social cognition have been reported with regard to the ability to recognize emotions in others (Abbott, Wijeratne, Hughes, Perre, & Lindell, 2014;Leite, Guerreiro, Almeida, & Peixoto, 2017;Nijsse, Spikman, Visser-Meily, de Kort, & van Heugten, 2019b;Yuvaraj et al, 2013) and the ability to reason about one's own and others' beliefs, feelings, intentions and knowledge (theory of mind; ToM) (Hamilton, Radlak, Morris, & Phillips, 2017;Martín-Rodríguez & León-Carrión, 2010;Nijsse et al, 2019b;Yeh & Tsai, 2014). Findings are mixed for the domain of empathy, with some (Hillis, 2014;Leigh et al, 2013;Yeh & Tsai, 2014) but not all studies reporting a decrease in sharing of emotions and feeling with another's feelings (Nijsse et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In stroke patients, impairments in social cognition have been reported with regard to the ability to recognize emotions in others (Abbott, Wijeratne, Hughes, Perre, & Lindell, 2014;Leite, Guerreiro, Almeida, & Peixoto, 2017;Nijsse, Spikman, Visser-Meily, de Kort, & van Heugten, 2019b;Yuvaraj et al, 2013) and the ability to reason about one's own and others' beliefs, feelings, intentions and knowledge (theory of mind; ToM) (Hamilton, Radlak, Morris, & Phillips, 2017;Martín-Rodríguez & León-Carrión, 2010;Nijsse et al, 2019b;Yeh & Tsai, 2014). Findings are mixed for the domain of empathy, with some (Hillis, 2014;Leigh et al, 2013;Yeh & Tsai, 2014) but not all studies reporting a decrease in sharing of emotions and feeling with another's feelings (Nijsse et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…Findings are mixed for the domain of empathy, with some (Hillis, 2014;Leigh et al, 2013;Yeh & Tsai, 2014) but not all studies reporting a decrease in sharing of emotions and feeling with another's feelings (Nijsse et al, 2019b). Most research on social cognition after stroke aimed to determine its neural underpinnings, specifically lateralization of impairments (Baldo, Kacinik, Moncrief, Beghin, & Dronkers, 2016;Hamilton et al, 2017;Yeh & Tsai, 2014;Yeh, Lo, Tsai, & Tsai, 2015;Yuvaraj et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Abbott et al, 2014a;Cooper et al, 2014) and others finding greater impairment for strokes lateralised to the right relative to the left hemisphere (e.g. Hamilton et al, 2017). Nonetheless, this highlights a potentially important distinction with regard to stroke categorisation.…”
Section: Neural Basis Of Social Cognition and Relationship To Strokementioning
confidence: 60%
“…Indeed, the research to date that has been conducted in this area has typically identified significant social cognitive impairment following stroke (e.g. Blonder et al, 2012;Cooper et al, 2014;Hamilton, Radlak, Morris & Phillips, 2017;Happé Brownell & Winner, 1999;Yeh & Tsai, 2014;Yuvaraj, Murugappan, Norlinah, Sundaraj & Khairiyah, 2013). However, some stroke patients may be more vulnerable to difficulties than others.…”
Section: Neural Basis Of Social Cognition and Relationship To Strokementioning
confidence: 99%
See 1 more Smart Citation